Imagining the nation through football: German national self-stereotypes before, during and after the 2016 UEFA championship. Issue 3 (3rd July 2022) - Mutz, Michael; Gerke, Markus; Meier, Henk Erik
Abstract: Previous research has shown that consuming media broadcasts of national athletes participating in international sporting competitions can inspire national pride and heighten identification with the nation. Extending these accounts, this paper asks whether major sporting events can also shape meanings attached to the nation; specifically how strongly certain traits and characteristics are associated with the collective. Since prior research shows that TV broadcasts of international sporting competitions prioritise their own nation's athletes and frequently draw on national stereotypes in their commentary, we hypothesise that these sportscasts have the potential to heighten the association of the nation with national stereotypes in TV viewers. Using large-scale, representative panel data from Germany, the paper tests these assumptions. Findings demonstrate that German TV viewers associated their nation more strongly with characteristics like achievement, diligence and solidarity during the 2016 UEFA football championship than at a baseline assessment about four weeks earlier. We find more pronounced effects among certain football-affine groups, who are socially and emotionally more strongly involved. Even two months after the conclusion of the event, a stronger association of the German nation with these particular traits was detectable in these groups, lending support to the notion that effects are more than just a short-term by-product of national euphoria.